Kompetensi Managerial Jabatan Administrasi Pegawai Negeri Sipil: Masalah dan Prospek Kebijakan - Mid Rahmalia (Pusat Pembinaan Jabatan Fungsional Bidang Pengembangan Kompetensi Pegawai ASN, 2020)
The development of civil servant competencies, especially the development of managerial competencies, is one of the mandates carried out by the State Administration Agency as stipulated in Law number 5 of 2014 and Government Regulation number 11 of 2017. Over time the dynamics of the organization create policy conditions as directed and policy strategies of President Joko Widodo who want the abolition of echelon III and echelon IV by carrying out the 2020 work program for simplifying bureaucracy through strategies using artificial intelligence. The Jokowi’s policy strategy brings its own challenges or challenges for the engineering of ASN training, especially civil servants in administrative positions to develop their competencies in line with environmental demands, namely to be able to form ASN Human Resources who are characterized in the current digital era. The question that arises is whether in the future it is necessary to have managerial training for the Administrative Officer or the head of the work unit if all are based on artificial intelligence? This study seeks to examine and explore the level of managerial ability of Level IV leaders and Level III Leaders in the Central and Regional Government organizational units, using three indicators that reflect Indicator I Readiness to be the leader of low-middle management; Indicator II Manage information and solve problems; and Indicator III Ability to build high performance quality. The results of the study provide a general picture that there are problems / deficiencies in managerial skills possessed by Leaders of Level IV and Leaders of Level III (referring to the applicable laws and regulations called Supervisors and Administrators). On average, the managerial skills of Level IV Leaders and Level III leaders need to be improved. Capacity building that must be done is on the three indicators measured. Related to the strategy of using artificial intelligence in the bureaucracy, it must start with the fulfillment of the Human Resources competency gap in managing management information systems that are still weak and need improvement. Whereas the prospect of the policy is the managerial competency development policy for the head of the work unit / manager of the organizational unit or the level of Supervisors and Administrators as well as the Functional Position who have the additional task of managing the work unit. Civil Servants certainly pay attention to the demands and needs of the organization.